Pregnancy and the pandemic H1N1 influenza virus: experiences in Leicester including the women referred for extracorporeal membrane oxygenation. (16th November 2010) - Moronke, A; Faulkner, G; Siddiqui, F; Roy, C; Firmin, R
Abstract : Since April 2009, the novel pandemic A/H1N1 influenza virus began causing illness in the UK. While causing mild flu-like symptoms in the majority of cases, the virus has been also identified as the cause of an outbreak of febrile respiratory infection. 34 confirmed cases of pandemic H1N1 in pregnant women were admitted to the maternity unit in Leicester. Leicester Glenfield Hospital is the 'front door' for access to adult extracorporeal membrane oxygenation (ECMO) in the UK. In consequence, our experiences reflect the severe end of the clinical spectrum. The authors summarised cases of infection with pandemic H1N1 virus in pregnant women in Leicester between April and December 2009. Pregnant women represent approximately 1% of the general population of the UK. Three of the 11 patients (18.2%) admitted to the intensive care unit at Leicester Royal Infirmary, with the confirmed 2009 H1N1 influenza were pregnant women. Of the 53 patients referred for ECMO, 18 (34%) were pregnant or recently delivered. When compared to the non-pregnant cohort, perinatal women are at risk of severe respiratory failure. Adult respiratory distress syndrome requiring respiratory support is a documented complicated of the H1N1 influenza virus. ECMO support when conventional ventillatory methods have failed, improves the respiratory function. Pregnant or recently delivered women were over represented in the groups admitted for respiratory support, and experience a more complicated recovery. These data lend support to the present recommendation to promptly treat pregnant women with H1N1 influenza virus infection with anti-flu drugs and encourage the vaccination programme in pregnant women.